Cutaneous Warts and Their Treatment Through Intralesional Vitamin D3 - Maria Farooqi, Raafia Ali, Azmat Fatema, Syed Mohammad Khizar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The Human Papilloma Virus (HPV) causes benign epidermal proliferation of the skin and mucosa. This proliferation of the skin is called warts. For the treatment of warts, a better method is being used widely over the last few years which is called intralesional immunotherapy. This method can be painful but it strengthens the cell-mediated immunity against HPV. Objective: The purpose of our research was to study cutaneous warts and determine the efficiency and safety of intralesional vitamin D3 in them. Moreover, we also evaluated their effects by assessing the results of the treatment. Study design: A cross-sectional study Place and Duration: This multi centric study was conducted in multiple dermatology centers of Saudi Arabia from August 2021 to August 2022 Methodology: A total of 50 patients were a part of this research. Every patient was above 18 years of age. They were given a maximum of 5 injections that were injected with an interval of 2 weeks. The injection of vitamin D3 was used in this research. 600k IU of cholecalciferol is contained in the vials in 1 ml. Lignocaine (0.2 ml) was first injected into the selected warts. Later in a few minutes, into the base of each wart, vitamin D3 (0.2 ml) was injected. After the treatment, every individual was observed for the next 6 months to detect the reduction in the size of warts or whether there is any recurrence. Results: Out of 50 individuals, the majority of them were having palmoplantar warts. There were 29 people who were having palmoplantar warts. Moreover, there were 10 individuals who were having common warts, 5 patients who had filiform warts, and the rest 6 individuals who were having periungual warts. There were 40 patients who showed a 100 percent response (complete response). A total of 5 participants showed a mild response and the rest 5 showed a moderate response. There were 4 patients in which the recurrence of warts was noted. Lastly, there were no serious effects reported. Conclusion: The most safe and effective treatment for multiple cutaneous warts is Intralesional vitamin D3. Keywords: Common warts, Intralesional vitamin D3, efficacy, adults, palmoplantar warts